Optimization of Extrusion Parameters and Feed Composition for Enhanced Quality of Millet Extrudates: OPTIMIZATION OF EXTRUSION PARAMETERS IN MILLETS - Srivastava, Soma; Jain, Dilip; Gupta, Neeraj (Annals of Arid Zone, 2024)
Extrudates prepared from cereal grains, such as corn, wheat, rice, and other starch-rich grains, are the second largest contributors to the global ready-to-eat snack market. These cereals contain optimal characteristics, like amount, type and particle size of starch/protein which are important for starch gelatinisation, viscosity and flow characteristics. These factors contribute to the rheology and organoleptic characteristics of the extrudates. In recent years, there has been a significant push in the utilization of the millets for development of extrusion products as they are ready-to-eat and considered as healthier. Major issues with 100% millet incorporation are dark colour, lower expansion, harder and denser extrudates and lower shelf life. In case of millets feed moisture (9-12%), barrel temperature (120-150°C) and screw (123-460 rpm) speed have favorable impact on expansion ratio and bulk density. Addition of starch containing cereals, legumes and hydrocolloids like sodium alginate and carboxymethylcellulose enhances expansion, lighten color and increases nutritional and health benefits. The aim of this review is to highlight the potential of extrusion technology for development of millet products, role of extrusion operating conditions and their effect on product parameters. The review also provides detailed insights about application of extrusion based 3-D printing, hot melt extrusion, hydrogel forming extrusion, centrifugal co-extrusion and extrusion-based encapsulation for the development of innovative millet based novel product development.